DEVISING A MARKING CRITERIA FOR THE ASSESSMENT OF AUDIOVISUAL TRANSLATION PRODUCTS IN AN ACADEMIC CONTEXT - Alvin Taufik (Universitas Bunda Mulia, 2022)
Although publications on audiovisual translation are gaining more and more attention, very little has been done on its assessment (Kajzer-Wietrzny & Tymczyńska, 2015). In the workfield, audiovisual translation is reviewed to be given ffedback. In Universitas Bunda Mulia (UBM), audiovisual translation assessments need to be objectively assessed to produce grades, in addition to individual and collective feedbacks. However, the grading in UBM has always been conducted subjectively. Subjective assessment might result in emotional judgment and inappropriate feedbacks. For that reason, this research aims to devise a marking criteria for the assessment of audiovisual translation products in an academic context, namely in UBM. The audiovisual translation in UBM is divided into four categories, namely captioning, subtitling, audio description, and dubbing. The marking categories to be used on each category needs to have different criteria. This research determines the criteria to be assessed based on market requirements as written in different literature. The criteria specifically developed in this research are those of captioning and dubbing. Both criteria is developed with translation or rendering accuracy as the most significant criteria, followed by synchronies and alignment as the second most significant criteria, and followed by equal values in formatting and technical accuracies. These criteria needs to be further tested for reliability and validity. In addition, training of the schemes must be administered considering that there are numerous specific terminologies used in them.